PENGARUH SOCIAL MEDIA MARKETING DAN WORD OF MOUTH TERHADAP PURCHASE DECISION DENGAN GROUP REFERENCE SEBAGAI VARIABEL MEDIASI (Studi Kasus Pada Pengguna Jasa Rias di Wilayah Kabupaten Pasuruan) - Keren Happuch Risananda Rosandy; Syaifuddin Fahmi (Jurnal Ilmiah Hospitality, 2022)
This study aims to examine the effect of social media marketing and word of mouth on purchase decisions of makeup service users in the Pasuruan Regency, East Java. Group Reference is used as a mediating variable which is expected to play a role in the relationship between the independent variable and the dependent variable. The research method used is by conducting surveys to consumers using questionnaires. The population used is the users of make-up services in the Pasuruan Regency with a sample size of 160 respondents. The method of determining the sample and collecting data using accidental sampling. The data obtained were then processed and analyzed using multiple linear regression and path analysis. The results of this study are social media marketing has a direct influence on the reference group variable and on the purchase decision variable. Word of mouth was also found to have a direct influence on the reference group variable and on the purchase decision variable. Meanwhile, the influence of social media marketing and word of mouth on purchase decisions through group reference as a mediating variable proved to have a significant effect.